The World of Gaming: Beyond a Hobby - Gavriil, Andriani (Open Schools Journal for Open Science, 2025)
In today’s digital era, gaming has evolved from a niche hobby into a global cultural and economic force. This talk explores the history, impacts, and future of gaming, addressing both its benefits and drawbacks. While often criticized for promoting violence and addiction, gaming also fosters social connection, cognitive development, and innovation. By examining the origins, influence, and future potential of gaming, this presentation highlights its significance beyond mere entertainment.